2022
DOI: 10.1080/20002297.2022.2146378
|View full text |Cite
|
Sign up to set email alerts
|

Tumour microbiota structure predicts hypopharyngeal carcinoma recurrence and metastasis

Abstract: Objectives The relationship between microbiota and HPSCC recurrence and metastasis remains uncertain. This study aimed to investigate the role of the tumour microbiota in the disease-free survival (DFS) of HPSCC patients. Materials and methods Formalin-fixed paraffin-embedded (FFPE) tumour tissues were collected from 103 patients with HPSCC for 16S rRNA sequencing. We analysed the tumour microbiota in HPSCC patients with recurrence/metastasis and nonrecurrence/metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…We explored the relationship between PVTT and tumors using an mIHC assay. Some high-impact studies have collected FFPE as experimental samples to explore the relationship between tumor microbiota and cancer development, providing further support for the reliability of our approach and results ( 10 ). Cao et al ( 11 ) collected 166 paraffin-embedded tumor tissues and 24 frozen tumor tissues to investigate the prognostic effects of the systemic inflammation response index on the survival of colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 57%
“…We explored the relationship between PVTT and tumors using an mIHC assay. Some high-impact studies have collected FFPE as experimental samples to explore the relationship between tumor microbiota and cancer development, providing further support for the reliability of our approach and results ( 10 ). Cao et al ( 11 ) collected 166 paraffin-embedded tumor tissues and 24 frozen tumor tissues to investigate the prognostic effects of the systemic inflammation response index on the survival of colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 57%
“…Eubacterium_coprostanoligenes_group and Prevotella were independent predictors of disease-free survival. The predicting classifier for recurrence and metastasis risk yielded an area under the curve of 0.83 at 3 years and 0.86 at 5 years [ 29 ]. Consistent with previous studies, our study focused on patients with a large tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…In response to identification of Eubacterium coprostanoligenes group as beneficial, we also found that patients with higher Eubacterium coprostanoligenes group abundance exhibited better progression-free survival. In addition, Yuan et al (2023) used Eubacterium coprostanoligenes group and Prevotella in construction of a model to estimate the risk of recurrence in patients with hypopharyngeal squamous cell carcinoma, and found that lower abundance of Eubacterium coprostanoligenes group was associated with higher recurrence and metastasis rates. Eubacterium_coprostanoligenes_group refers to a group of anaerobic Gram-positive bacteria involved in cholesterol transformation and regulation of cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%